1989
DOI: 10.1111/j.1752-1688.1989.tb05406.x
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATING MEAN AND VARIANCE FOR ENVIRONMENTAL SAMPLES WITH BELOW DETECTION LIMIT OBSERVATIONS1

Abstract: Left-censoring of data sets complicates subsequent statistical analyses. Generally, substitution or deletion methods provide poor estimates of the mean and variance of censored samples. These substitution and deletion methods include the use of values above the detection limit (DL) only, or substitution of 0, DLI2 or the DL for the below DL values during the calculation of mean and variance. A variety of statistical methods provides better estimators for different types of distributions and censoring. Maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
4

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 44 publications
0
59
0
4
Order By: Relevance
“…These data, combined with the measurements above the nominal detection limit, were sorted and used to prepare a cumulative probability graph. The gee-statistical analysis was performed in Microsoft EXCEL as described in Newman et al (1989) -see method description for "order statistics." The results were checked using the PROBPLOT program (Stanley, 1987) distributed by the Association of Exploration Geochemists.…”
Section: Probability Plotsmentioning
confidence: 99%
“…These data, combined with the measurements above the nominal detection limit, were sorted and used to prepare a cumulative probability graph. The gee-statistical analysis was performed in Microsoft EXCEL as described in Newman et al (1989) -see method description for "order statistics." The results were checked using the PROBPLOT program (Stanley, 1987) distributed by the Association of Exploration Geochemists.…”
Section: Probability Plotsmentioning
confidence: 99%
“…Concentrations of total phosphorus and ammonium in water below the detection limit of the methods (9.0 µg dm -3 for total phosphorus and 18.0 µg dm -3 for ammonium) were changed to half of these values for use in the graphics and statistical analyses, as suggested by Newman et al (1989), Lewis et al (2007), andDDE (2012). We adopted this procedure in order to avoid unnecessary loss of information.…”
Section: Coordinates Measured With Utm Wgs Datum 84mentioning
confidence: 99%
“…However, the use of zeros "leftcensors" the database by removing values at the lowest range of the analysis; this results in lower means and increased standard deviations within each field (Newman et al 1989). For the HBES chemical dataset before 1990, a zero indicated that the value was below the minimum reportable concentration (MRC).…”
Section: Quality Assurance Proceduresmentioning
confidence: 99%